The Analysis of Understanding English Reading Text In Uinsu Students MPI Prodi 2 - Lubis, Yani; Sukmawan, Indah; Asri, Dwi; Safitri, Rizki Rahmadani (Madani: Jurnal Ilmiah Multidisiplin, 2024)
The purpose of this research is to understand how to increase the understanding of how to read English for students of the second semester of the Islamic Education Management study program, so that they can read comfortably, understand the meaning of each word, sentence and paragraph without looking at the dictionary when reading. carried out using qualitative methods starting from direct observation to the MPI 2 student class, interviews were also carried out with several students, and finally we took documentation during the interview process, so that we received the correct results. The achievements of this research show that students' English reading comprehension has improved significantly from the previous semester, students have also understood the meaning of English reading texts by just listening to them. The method they use to improve their understanding is by continuing to read English regularly, and memorizing lists of words. By increasing the list of words, we as students can improve our reading comprehension. These are the two methods that the average student uses.